A Conceptual Review of Demerit Points as Punishment and Social Necessity (Journal of Applied Learning and Teaching, 2020)
Research suggests that students are aware of how much time they spend using electronics for non-academic activities during class. Many students believe they are multitasking when they engage in distracted behavior in the classroom. To make matters worse, many educators have become complacent and ignore or tolerate the use of electronics because they have no way to effectively solve the problem. Studies show that the use of electronics, such as a laptop computer or a smartphone, can distract as many as six other people seated near that student. Students engaged in distracting behavior negatively impact the learning and teaching of course content for themselves and others around them. The problem has impacted all levels of education from grade school to college. Studies of motivation theory have provided significant evidence that students are motivated by educators who exercise strong classroom-management skills. A demerit system in which points are lost will significantly reduce unwanted student behavior in the classroom, specifically the use of electronic devices for non-academic activities, resulting in increased achievement as measured by the final exam. This solution can also be generalized to any classroom setting where students earn points.